Reducing the data-deficiency of threatened European habitats: Spatial variation of sabellariid worm reefs and associated fauna in the Sicily Channel, Mediterranean Sea. (September 2017) - Bertocci, Iacopo; Badalamenti, Fabio; Lo Brutto, Sabrina; Mikac, Barbara; Pipitone, Carlo; Schimmenti, Eugenia; Vega Fernández, Tomás; Musco, Luigi
Abstract: Biogenic reefs, such as those produced by tube-dwelling polychaetes of the genus Sabellaria, are valuable marine habitats which are a focus of protection according to European legislation. The achievement of this goal is potentially hindered by the lack of essential empirical data, especially in the Mediterranean Sea. This study addresses some of the current knowledge gaps by quantifying and comparing multi-scale patterns of abundance and distribution of two habitat-forming species ( Sabellaria alveolata and S. spinulosa ) and their associated fauna along 190 km of coast on the Italian side of the Sicily Channel. While the abundance of the two sabellariids and the total number of associated taxa did not differ at any of the examined scales (from tens of centimetres to tens-100 of kilometres), the structure (composition in terms of both the identity and the relative abundance of constituting taxa) of the associated fauna and the abundance of several taxa (the polychaetes Eulalia ornata, Syllis pulvinata, S. garciai, Nereis splendida and Arabella iricolor, and the amphipods Apolochus neapolitanus, Tethylembos viguieri and Caprella acanthifera ) varied among locations established ∼50–100 km apart. Syllis pulvinata also showed significant variation between sites (hundreds of metres apart), analogously to the other syllid polychaetes S. armillaris and S. gracilis, the nereidid polychaete Nereis rava, and the amphipod Gammaropsis ulrici . The largest variance of S. spinulosa, of the structure of the whole associated fauna and of 56% of taxa analysed individually occurred at the scale of replicates (metres apart), while that of the dominant bio-constructor S. alveolata and of 25% of taxa occurred at the scale of sites. The remaining 19% and the total richness of taxa showed the largest variance at the scale of locations. Present findings contribute to meet a crucial requirement of any future effective protection strategy, i.e., identifying relevant scales of variation to be included in protection schemes aiming at preserving representative samples not only of target habitats and organisms, but also of the processes driving such variability. Highlights: Sabellaria worm reefs and associated fauna were investigated in the Sicily Channel. Spatial scales from tens of centimetres to tens of kilometres were examined. The abundance of habitat-formers and the richness of associated taxa did not differ at any scale. Despite taxon-specific variation, small-scale variance tended to be the most relevant. Present findings have implications for protection measures, monitoring and restoration.